Modelling and performance analysis of an innovative CPVT, wind and biogas integrated comprehensive energy system: An energy and exergy approach. (1st April 2020) - Bamisile, Olusola; Huang, Qi; Li, Jian; Dagbasi, Mustafa; Desire Kemena, Awoh; Abid, Muhammad; Hu, Weihao
Graphical abstract: Highlights: Energy and exergy analysis a CPVT and wind turbine integrated comprehensive system. Integration of biogas powered systems as a backup system and modelling based on four scenarios. Overall energy efficiency considering all the case studies, ranges from 64.91% to 71.06%. Also, overall exergy efficiency ranges from 31.80% to 53.81%. Maximum CO2 emission reduction in comparison to coal fired system is 2680.4 kg/h. Abstract: One of the challenges faced by renewable energy (RE) powered multigeneration system is the unavailability of RE resources at different times. In this research, a novel comprehensive energy system powered with wind turbines, concentrated photovoltaic/thermal and biogas is modelled and analyzed using energy and exergy approach. Multiple useful products such as electricity, hot air, hydrogen, fresh water, cooling effect and hot water will be produced by the system. Four different operational scenarios namely; CPVT/wind, wind/biogas, CPVT/biogas, and biogas only are considered for this comprehensive energy system. Thermal energy storage is incorporated with the system, in order to save thermal energy that will be used during hours without solar radiation. Furthermore, the CO2 emissions saved, in comparison with the use of different fossil fuel sources is analyzed. The maximum productions from the comprehensive system are: 3.4 MW of electricity; 12.41 L/sec of Hydrogen; 279.4 kW of cooling effect; 17.546 kg/s of hot air; 144.18 L/min of hot water and 10.31 L/min of fresh water. The overall energetic efficiency of the system considering all the case studies ranges from 64.91% to 71.06% while the exergetic efficiencies ranges from 31.80% to 53.81%. The CO2 emission analysis results show that the system is environmentally friendly.